Leading with knowledge the nature of competition in the 21st century - Huseman, Richard C.; Goodman, Jon P.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
The intellectual assets of a corporation can be leveraged to create a knowledge organization and this book details the forces of change which companies must respond to, and describes the techniques used to restructure organizations.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge management; Organizational learning; Organizational change; Employees -- Training of; Electronic books